Loss of Autophagy Causes Increased Apoptosis of Tibial Plateau Chondrocytes in Guinea Pigs with Spontaneous Osteoarthritis. (December 2021) - Wang, Xiao-jian; Tian, Wei; Xu, Wei-wei; Lu, Xiao; Zhang, Yu-ming; Li, Li-jun; Chang, Feng
Objective: The goal of the present study was to observe the effect of autophagy in tibial plateau chondrocytes on apoptosis in spontaneous knee osteoarthritis (OA) in guinea pigs. Design: Fifty 2-month-old female Hartley guinea pigs were divided into a normal group (10 animals, all euthanized after 7 months) and an OA group (40 animals, 10 of which were euthanized after 10 months). Immunohistochemistry, RT-qPCR and Western blotting were used to evaluate autophagy levels, intracellular glycogen accumulation and apoptosis in tibial plateau chondrocytes in vivo and in vitro . The remaining 30 guinea pigs in the OA group were divided into 3 groups: a rapamycin group, a normal saline group, and a 3-methyladenine (3-MA) group. Intracellular glycogen accumulation and chondrocyte apoptosis were assessed by altering the level of autophagy in chondrocytes in vivo . Results: When spontaneous OA occurred in guinea pigs, autophagy levels in tibial plateau chondrocytes decreased, while intracellular glycogen accumulation and the rate of chondrocyte apoptosis increased. After enhancing the level of autophagy in tibial plateau chondrocytes in guinea pigs with OA, intracellular glycogen accumulation and the rate of chondrocyte apoptosis decreased, while inhibiting autophagy had the opposite effects. Conclusion: The results indicate that the function of autophagy in chondrocytes may at least partly involve the catabolism of glycogen. In guinea pigs with OA, the level of autophagy in tibial plateau chondrocytes decreased, and chondrocytes were unable to degrade intracellular glycogen into glucose, leading to less energy for chondrocytes and increased apoptosis.